2014
DOI: 10.1089/apc.2014.0046
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Positive Men's Experiences with Integrated Family Planning and HIV Services in Western Kenya: Integration Fosters Male Involvement

Abstract: A growing body of evidence indicates that integrating family planning (FP) services into HIV care is effective at improving contraceptive uptake among HIV-positive women in resource-poor settings, yet little research has examined HIV-positive men's experiences with such integration. We conducted in-depth interviews with 21 HIV-positive men seeking care at HIV clinics in Nyanza, Kenya. All clinics were intervention sites for a FP/ HIV service integration cluster-randomized trial. Grounded theory was used to cod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 45 publications
(56 reference statements)
2
21
0
Order By: Relevance
“…The predominance of age lower than 39 years, steady relationship, and low household income among the study participants showed that women of reproductive age and socio-economic vulnerability were exposed to the virus through sexual transmission, in conformity with other studies (4,(12)(13) . According to the current research, after diagnosis women with HIV/AIDS continued working actively to guarantee the income of their children and partners (14) .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The predominance of age lower than 39 years, steady relationship, and low household income among the study participants showed that women of reproductive age and socio-economic vulnerability were exposed to the virus through sexual transmission, in conformity with other studies (4,(12)(13) . According to the current research, after diagnosis women with HIV/AIDS continued working actively to guarantee the income of their children and partners (14) .…”
Section: Discussionsupporting
confidence: 89%
“…Evidence shows that maternity is an important motivation for women with HIV/AIDS to continue with their life plans and adhere to the treatment (15) . Despite the fact that most of the women with AIDS were within reproductive age and had active sexual lives, many did not want to have children in the future, a similar finding to that of other studies (9)(10)12) . In the current research, this aspect could be associated with the fact that women have a lower household income, already had children, or it could be related to the lack of opportunity to discuss aspects related to reproduction with health professionals.…”
Section: Discussionsupporting
confidence: 79%
“…Gender power dynamics likely also impact HIV risk behaviors independently of individual motivation and behavior. 18,[37][38][39] Our findings suggested that women gained power in the relationship by having children, perhaps by legitimizing the union with biological children desired by male partners. Women uncertain about conception described raising concerns regarding pregnancy and HIV risk with their partners, but ultimately the couples' decision to conceive conceded to the male partners' desires.…”
Section: Discussionmentioning
confidence: 69%
“…Thus, power dynamics are not fixed or unchangeable and are fluid, at play, and contested (Messner 1997; Peacock et al 2009). Our group’s previous work has hypothesised that integrating family planning with HIV care may allow for more open interactions between partners around contraceptive decision-making (Newmann, Grossman et al 2013; Patel et al 2014; Tao et al 2015). This study suggests that when family planning becomes medicalised in the HIV care setting, health professionals’ opinions and the goal of staying healthy may shift or supplant male-dominated patterns of resistance to family planning.…”
Section: Discussionmentioning
confidence: 99%